Enhanced photoluminescence quantum yield of Ce3+‐doped aluminum–silicate glasses for scintillation application. Issue 1 (17th September 2022) - Wu, Tao; Hua, Zhehao; Tang, Gao; Ban, Huiyun; Cai, Hua; Han, Jifeng; Liu, Hui; Liu, Shan; Qian, Sen; Qin, Laishun; Ren, Jing; Sun, Xilei; et al.
Abstract: Ce 3+ ‐doped 20Gd2 O3 –20Al2 O3 –60SiO2 (GAS: x Ce 3+ ) glasses ( x = 0.3, 0.7, 1.1, 1.5, 1.9 mol%) with Si3 N4 as a reducing agent were prepared. The density of the glasses is around 4.2 g/cm 3 . With the increase in the Ce 3+ concentration, both the photoluminescence (PL) and PL excitation peaks of GAS: x Ce 3+ glasses show a redshift because the 4f–5d energy levels of Ce 3+ ions are narrowed. PL quantum yield and PL decay time of GAS: x Ce 3+ glasses are 28.32–50.59% and 43–64 ns, respectively. In addition, they both first increases and then decreases with the Ce 3+ concentration increasing, reached the maximum when x = 1.1 mol%. The integrated X‐ray excited luminescence (XEL) intensity of the GAS:1.1Ce 3+ glass is 23.86% of that of Bi4 Ge3 O12 (BGO) crystal, and the light yield reaches 1200 ph/MeV with an energy resolution of 22.98% at 662 keV when exposed to γ‐rays. The PL and XEL thermal activation energies of GAS: x Ce 3+ glasses are independent of Ce 3+ ions concentration. Scintillating decay time of the glasses exhibits two components consisting of nanosecond and microsecond levels, and the scintillating decay time gradually decreases with the Ce 3+ concentration increasing. The difference between PL and scintillating decay time is discussed regarding the different luminescent mechanisms. Abstract :